2017
DOI: 10.1007/s12105-017-0859-1
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Carcinoma of the Buccal Mucosa and Lower Lip

Abstract: Merkel cell carcinoma (MCC) is an uncommon relatively aggressive neuroendocrine dermal neoplasm first described in 1972 as a tumor of the sun exposed skin. Although most MCC affect the skin of the head and neck, rare primarily oral mucosal cases have been documented. Merkel cells are nondendritic neuroendocrine cells that are found not only in the skin but also the oral mucosa and give rise to MCC. Neuroendocrine cells may be found as aggregates in organs or as diffuse or isolated cells within organs and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…MCC was first described in 1972 by Cyril Toker as a trabecular skin carcinoma. Later, the tumor name was modified to MCC given the similarity in appearance and ultrastructure between tumor cells and Merkel cells, the mechanoreceptors of the basal epidermal layer of the skin 20 . Both MCC subtypes are characterized by different stages, including localized, regional, and distant metastasis 21 .…”
Section: Causes Therapy Diagnosis and Prognosismentioning
confidence: 99%
“…MCC was first described in 1972 by Cyril Toker as a trabecular skin carcinoma. Later, the tumor name was modified to MCC given the similarity in appearance and ultrastructure between tumor cells and Merkel cells, the mechanoreceptors of the basal epidermal layer of the skin 20 . Both MCC subtypes are characterized by different stages, including localized, regional, and distant metastasis 21 .…”
Section: Causes Therapy Diagnosis and Prognosismentioning
confidence: 99%
“…The estimated three-year survival of MCC has been reported as low as 50%. [4] In conclusion, mucosal MCC is an uncommon and aggressive neuroendocrine neoplasm with a high risk for recurrence and distant metastasis. It should be considered in the differential diagnosis of head and neck mucosal lesions.…”
Section: Discussionmentioning
confidence: 91%
“…At time of diagnosis most lesions have metastasized to the regional lymph nodes. [4] Histopathologically, the tumor shows small, round to ovoid primitive looking cells with a strong acidophilic staining with a salt-andpepper-like nuclei and inconspicuous nucleoli. The IHC staining is an important ancillary test for diagnosing MCC.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 2008, a cohort study following 195 patients found 88% of MCCs were nontender [9]. Merkel cell carcinoma of the mandibular or submandibular glad is extremely rare and there are only a handful of case reports on this topic, although MCC is well known to affect the skin of the head and neck [10,11].…”
Section: Discussionmentioning
confidence: 99%